Development of Sharia Monetary Policy in the Indonesian Economic System (Study of Islamic Bank Interest Monetary Policy): Studi Kebijakan Moneter Bunga Bank Syariah - Hermawan, Daniel; Helmi, Hamdi; Sihotang, Desjantri; Pratama, Rahmadiansyah; Rossevelt, Franklin Asido (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Monetary policy issued by the central bank is useful for realizing the economic aspirations expected by a country, namely realizing and maintaining the stability of currency values. Monetary policy in the definition of Islam adheres to the basic principles of Islamic economics, namely having the highest power to Allah SWT, where everything that is owned by humans on earth is with the permission of Allah SWT. The purpose of this study is to explain the development of Islamic monetary policy in the Indonesian economic system. This study uses the literature review method, which examines theories related to the problems in this research. Literature review is done through data collection or relevant journals.